A focus on coordination chemistry at chlorine. Issue 15 (28th March 2023) - Dutton, Jason L.
Abstract : A highlight of the recent report on the remarkable outcomes of the seemingly simple reaction of pyridines with chlorine gas. Abstract : The first crystallographic characterization of chloronium cations stabilized by pyridine ligands (P. Pröhm, W. Berg, S. M. Rupf, C. Müller and S. Riedel, Chem. Sci., 2023, ; https://doi.org/10.1039/D2SC06757A ) is discussed in the context of coordination chemistry at chlorine.